2010
DOI: 10.1007/s13277-010-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of anemia, leukocytosis, and thrombocytosis in patients with solid tumors in China

Abstract: Despite the fact that malignancies are associated with hematological abnormalities, some clinical studies have been unable to detect such a relation. The aim of our study was to detect the prevalence of pretreatment hematologic abnormalities in patients with common solid tumors and to determine if such a profile could be used for prognostic evaluations. We identified all patients in Cancer Center of Sun Yat-sen University who were diagnosed as solid tumors (breast carcinoma, hepatocellular carcinoma, nasophary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 30 publications
(40 reference statements)
8
54
3
2
Order By: Relevance
“…Interestingly, patients with preexisting anemia before therapy exhibit reduced survival following treatment for breast, lung, prostate, and other cancers (4,38). Our results support the hypothesis that breast cancer patients may develop anemia concomitant with disease severity or progression, a characteristic that may impact treatment options.…”
Section: Hoxa9 Ezh2supporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, patients with preexisting anemia before therapy exhibit reduced survival following treatment for breast, lung, prostate, and other cancers (4,38). Our results support the hypothesis that breast cancer patients may develop anemia concomitant with disease severity or progression, a characteristic that may impact treatment options.…”
Section: Hoxa9 Ezh2supporting
confidence: 77%
“…Blood was analyzed on the scil Vet abc hematology analyzer (scil animal care company) or treated with NH 4 Cl to lyse RBCs before flow cytometry.…”
Section: Tumor Injection and Tissue Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study by Kim in 2011 in South chorea the impact of duration of anemia while chemotherapy was done in patient with epithelial ovarian cancer was investigated. This study was shown that if hemoglobin lesser than 10 mg/dl lasted more than 20%of chemotherapy duration was associated with lower 5 years survival [18]. Causes of anemia in cancers are different included: iron metabolism disorders, extra corpuscular hemolysis and cell catabolism due to tumor invasion, and paracrine signaling factors such as interleukin-1, tumor necrosis factor [19].…”
Section: Discussionmentioning
confidence: 87%
“…Previously, evidence has indicated that anemia is correlated with poor clinical Preoperative mean corpuscular hemoglobin affecting long-term outcomes of hepatectomized patients with hepatocellular carcinoma prognosis in several cancer types (12)(13)(14)(15). In addition, in HCC, a previous report demonstrated the prognostic impact of hemoglobin (HGB) levels prior to treatment (16). The mean corpuscular hemoglobin (MCH), which refers to a measurement of the average HGB content of each red blood cell, is another anemia associated factor, which reflects iron metabolism.…”
Section: Introductionmentioning
confidence: 99%